2015
DOI: 10.1128/aac.05002-14
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Injury Associated with Telavancin Dosing Regimen in an Animal Model

Abstract: The elevation of serum creatinine levels is a concern with telavancin therapy. We examined the onset of kidney injury associated with telavancin in an animal model. Urine samples were collected at baseline and daily to determine the concentrations of kidney injury molecule 1 (KIM-1), a marker for early kidney injury. When a clinically relevant exposure of telavancin was given daily to rats, some differences in kidney injury were attributed to the dosing regimen. Further investigations of alternative telavancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…Except for day 4, there was no significant difference between treatment groups in shifts of CrCl levels that would have resulted in a telavancin dose modification (CrCl ≤50 ml/min). A similar effect with regard to the time course has been shown in a rat model of nephrotoxicity, in which telavancin was administered at clinically relevant exposures . The study demonstrated that elevations in KIM‐1, a marker of early renal injury, were most pronounced within the first 5 days of therapy, with a peak at about day 3, and then gradually returned to baseline levels.…”
Section: Discussionsupporting
confidence: 66%
“…Except for day 4, there was no significant difference between treatment groups in shifts of CrCl levels that would have resulted in a telavancin dose modification (CrCl ≤50 ml/min). A similar effect with regard to the time course has been shown in a rat model of nephrotoxicity, in which telavancin was administered at clinically relevant exposures . The study demonstrated that elevations in KIM‐1, a marker of early renal injury, were most pronounced within the first 5 days of therapy, with a peak at about day 3, and then gradually returned to baseline levels.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, 7.5 mg/kg BW achieved exposure levels in patients with up to moderate renal impairment that were comparable to the standard dose in subjects with normal kidney function, whereas for more severe forms 7.5 mg/kg results in overexposure. Moreover, a number of studies demonstrated that telavancin leads to increases in serum creatinine and exhibits a potential for nephrotoxicity [ 51 53 ].…”
Section: Influence Of Organ Impairment and Drug–drug Interactionsmentioning
confidence: 99%
“…Telavancin should thus be used with caution in patients predisposed to kidney dysfunction (pre-existing renal disease, diabetes mellitus, congestive heart failure, or hypertension) [10]. Studies in rats suggest that the onset of kidney injury depends on the dose and on the dosing interval (more rapid if a longer dosing interval) [161].…”
Section: Adverse Eventsmentioning
confidence: 99%